Intravitreal Injection of Sulfamethoxazole and Trimethoprim Associated with Dexamethasone as an Alternative Therapy for Ocular Toxoplasmosis. (3rd October 2018) - Souza, Carlos E.; Nascimento, Heloisa; Lima, Acácio; Muccioli, Cristina; Belfort, Rubens
ABSTRACT: Purpose : To evaluate intravitreal injections of sulfamethoxazole/trimethoprim in association with dexamethasone for treating toxoplasmic retinochoroiditis. Methods : Thirteen patients with active, recurrent ocular focal toxoplasmic retinochoroiditis and visual acuity worse than 20/63 in the affected eye were included. Ocular toxoplasmosis was diagnosed according to the classic clinical findings. The primary end point was the change in the final best-corrected visual acuity (BCVA). Results : The intraocular inflammation decreased within 2 weeks after injection in all eyes and resolved in 8 (62%) eyes with only one injection after 30 days; the remaining eyes received two injections. In all eyes, the retinitis was inactive and no patient had decreased early treatment diabetic retinopathy study lines of BCVA at the final examination. Conclusion : The combination of intravitreal trimethoprim/sulfamethoxazole and dexamethasone might be an alternative treatment strategy in patients with toxoplasmic retinochoroiditis.